BATU kENDAN DAN MANUSIA PRASEJARAH DI TEPIAN DANAU BANDUNG PURBA - Lutfi Yondri (Balai Arkeologi Kalimantan Selatan, 2010)
Based on archaeological data discovered on the bank of Danau Bandung purba, it can be inferred that human occupation had occurred during the Palaeolithic until Palaeometalic stage. Apparently until today, this area has become ‘primadona’ for dwelling site. In regard to the idealistic attribute for setting on the bank of Danau Bandung Purba was stone tools made of ‘batu kendan’ or obsidian which is assumed originated from the site. This Article discusses the relationship between human occupation on the Danau Bandung Purba and the available stone tool resources.